[PP.17.05] INTRADIALYTIC HYPOTENSION AND COGNITIVE FUNCTION IN MAINTENANCE HAEMODIALYSIS PATIENTS - ARE THEY RELATED?. (September 2016) - Radic, J.; Radic, M.; Kovacic, V.; Dodig Curkovic, K.; Sain, M.; Ljutic, D.
Abstract : Objective: Although a considerable number of article on cognitive function in maintenance HD patients have been published, little data are available about relationship between blood pressure and cognitive function. HD-associated hypotension is one of the main complications of HD and HD-associated hypotension increases mortality in this population of patients. The aim of the present study was to analyze the relationships between blood pressure before, during and after HD and cognitive performance. Design and method: Forty nine medically stable patients (aged 61.40 ± 10.84 years) on maintenance HD (3.80 ± 2.82 years) were investigated. Assessment of cognitive functions was performed by Trail Making Test-form A (TMT A) and Test of convergent thinking from the Complex Reactiometer Drenovac (CRD-series) system one hour before and one hour after the same HD session. Results of the cognitive abilities were given as total time of test solving in seconds. The systolic and diastolic blood pressure were measured on the beginning and at the end of HD. Data of hypotensive episodes (RR < 110/60 mmHg with symptoms and stuff interventions) were assessed from patients' records 3 months retrospectively from the cognitive testing period (36 HD sessions/subject were assessed). Results: Statistically significant correlation between numbers of hypotensive episodes during past three months prior study with total time needed to solve convergent thinking test after HD was found (r = 0.427, p = 0.002). The results showed that HD patients who have a larger number of hypotensive episodes during HD procedure needed more time (performed worse) to solve convergent thinking test. Therefore, statistically significant negative correlations between diastolic blood pressure at the end of the HD and total time in solving test of convergent thinking and total time in solving TMT-A test at the end of the HD were found (r = −0.263, p = 0.044), (r = −0.244, p = 0.044), respectively. Those patients with lower diastolic blood pressure after HD needed more time (performed worse) on cognitive tests. Conclusions: These results suggest that intradialytic hypotension may affect cognitive functions in maintenance HD patients. A further study is necessary to determine whether preventing HD-associated hypotension will improve cognitive performance in HD patients.